Spirituality in older adults and its health benefits: a systematic review - Aponte-Franco, Sandra Milena (2022)
Objective: to identify the benefits of spirituality in the health of the elderly. Method: narrative bibliographic review, a bibliographic search of original articles published during 2017-2021, in the databases PubMed, Tripdata Base, Cochrane, BVS, ScienceDirect and Lilacs was performed using the descriptors: spirituality, elderly, older adults and health in languages: Spanish, Portuguese and English, advanced search was performed and then compliance with the exclusion and inclusion criteria was verified, finally it was validated by applying methodological guidelines obtaining a sample of 25 documents.  Main results: the selected articles were qualitative, quantitative and mixed; following the content analysis, they were grouped into central categories: spirituality and positive attitude towards life and wellbeing; spirituality and strengthening of mental health; spirituality and biophysical wellbeing; spiritual care and the importance of its approach from nursing and health professionals. Main conclusions: the greatest interest in addressing spirituality in older adults is related to pathological processes and how to address them in a more effective way, in addition to improving their health-related behavior. For future studies, research is needed to deepen specific actions from health sciences, nursing and other areas of knowledge.